2000
DOI: 10.1136/adc.83.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid therapy in nephrotic syndrome: a meta-analysis of randomised controlled trials

Abstract: Conclusions-Children in their first episode of steroid responsive nephrotic syndrome should be treated with prednisone for at least three months, with an increase in benefit being shown for up to seven months of treatment. (Arch Dis Child 2000;83:45-51)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
3
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 18 publications
0
48
3
7
Order By: Relevance
“…Pemberian kortikosteroid menurunkan angka kematian dari 35% menjadi 3%. 8 Pemberian kortikosteroid dengan dosis tepat sesuai berat badan kering anak penting dalam menangani anak penderita SN karena toksisitas pemberian kortikosteroid berpotensi mengancam hidup sehingga risiko dan manfaat terapi harus terus dievaluasi.…”
Section: Pendahuluanunclassified
“…Pemberian kortikosteroid menurunkan angka kematian dari 35% menjadi 3%. 8 Pemberian kortikosteroid dengan dosis tepat sesuai berat badan kering anak penting dalam menangani anak penderita SN karena toksisitas pemberian kortikosteroid berpotensi mengancam hidup sehingga risiko dan manfaat terapi harus terus dievaluasi.…”
Section: Pendahuluanunclassified
“…In 2000 we published a systematic review of RCTs which evaluated corticosteroid therapy in children with their first episode of steroid-sensitive nephrotic syndrome (SSNS) [3]. In a meta-analysis of five RCTs (334 children), prednisolone administered for 3-7 months compared with 2 months in the initial episode of SSNS significantly reduced the risk of relapse at 12-24 months by 27 % [relative risk (RR) 0.73; 95 % confidence intervals (CI) 0.60-0.89) and reduced the number of children with frequently-relapsing nephrotic syndrome (FRNS) by 33 % (RR 0.67; 95 % CI 0.48-0.93).…”
Section: Combining the Evidence From Rctsmentioning
confidence: 99%
“…Thus, the heterogeneity among the studies can be explained by differences in methodological quality (risk of bias). The studies included in the systematic review published in 2000 [3] and in the updates to 2007 [4] were generally of high or unclear risk of bias. Only three studies showed adequate allocation concealment [12][13][14], and no studies were blinded.…”
Section: Investigation Of Heterogeneity In Meta-analysesmentioning
confidence: 99%
“…Research by Norero et al in 1996 which compared the ISKDC regimen with a 12 week prednisolone regimen also yielded similar results 22 . The meta-analysis by Hodson E, et al suggested that extension of alternate day steroid by one month reduces the risk of relapse at 2 years by 7% up to 7 months 3 . The Cochrane Database Systematic Review of 2015 suggests that there are many factors that determine the risk of relapse viz.…”
Section: Methodsmentioning
confidence: 99%
“…Nephrotic syndrome has an incidence of 2 to 7 per 100,000 Caucasian children with a higher incidence of about 16 per 100,000 in Asian children 2,3 . Steroid-sensitive NS remains the predominant type of NS during childhood with 90-95% children being responsive to steroids, of whom a greater proportion have minimal change nephropathy (MCN) 4 .…”
Section: Introductionmentioning
confidence: 99%